Polymer solid electrolyte membrane, preparation method thereof and solid lithium metal battery

The polymer solid electrolyte membrane is prepared by introducing a second solvent, which solves the problems of low conductivity and low film formation efficiency in the prior art, and realizes efficient and environmentally friendly electrolyte membrane preparation, which is suitable for the application of lithium-ion batteries.

CN119650866APending Publication Date: 2025-03-18HU ZHOU YAO NING GU TAI DIAN CHI YAN JIU YUAN YOU XIAN GONG SI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311192643.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing polymer solid electrolyte membrane has low ionic conductivity and low film formation efficiency, resulting in limited application in lithium-ion batteries.

Method used

The polymer solid electrolyte membrane is prepared by introducing a second solvent, and the polymer molecular chain movement state is quickly fixed by using the differences in the dissolving state of the polymer in different solvents, reducing the crystallinity of the polymer, avoiding the volatility of the high-temperature solvent, and improving the film formation efficiency.

Benefits of technology

It has achieved high ionic conductivity and high film formation efficiency of polymer solid electrolyte membranes, reduced energy consumption and environmental pollution, and has the potential for continuous production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650866A_ABST
    Figure CN119650866A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a polymer solid-state electrolyte membrane and a preparation method thereof and a solid-state lithium metal battery, and the method for preparing the polymer solid-state electrolyte membrane comprises the following steps: (1) carrying out first mixing on a polymer, a lithium salt, a plasticizer and a first solvent to obtain a polymer solid-state electrolyte solution; the first solvent is at least one of good solvents; (2) coating a substrate with the polymer solid electrolyte solution to obtain a substrate I containing the electrolyte solution; and (3) placing the substrate I in a second solvent for precipitation treatment to obtain the polymer solid electrolyte membrane, the second solvent is at least one of poor solvents; the volume ratio of the dosage of the first solvent to the dosage of the second solvent is 1: (0.2-5). The polymer solid electrolyte membrane provided by the invention has a membrane forming effect consistent with that of a traditional process, and is low in crystallinity and relatively high in ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a polymer solid electrolyte membrane and a preparation method thereof, and a solid lithium metal battery. Background Art

[0002] With the continuous development of the new energy industry, solid-state batteries have attracted widespread attention due to their advantages of high energy density and good safety compared to liquid batteries. Solid electrolytes are the core material components of solid-state batteries. Currently, there are three main types: polymer solid electrolytes, inorganic solid electrolytes and solid electrolytes. Among them, polymer solid electrolytes have attracted much attention due to their good flexibility and strong processability.

[0003] The low ionic conductivity of polymer solid electrolytes limits their application. Polymer solid electrolytes generally have the ability to crystallize, often forming a crystalline region and an amorphous region structure inside them. In the crystalline region, the polymer molecular chains are arranged regularly, and the molecular chains have weak free movement ability, resulting in poor lithium ion conductivity, which leads to low ionic conductivity of polymer solid electrolyte membranes. Therefore, reducing the crystallinity of the polymer will help improve the ionic conductivity of the polymer solid electrolyte membrane.

[0004] In addition, the common method for preparing polymer solid electrolyte membranes is the solution method, which forms a membrane by evaporating the solvent under high temperature conditions. This process is generally inefficient and is accompanied by the volatilization of organic solvents, which is not conducive to the continuous and rapid preparation of polymer solid electrolyte membranes.

[0005] CN106992311A discloses an all-solid polymer electrolyte membrane and a preparation method thereof, wherein the all-solid polymer electrolyte membrane uses PEO or PEO-PMMA as a matrix, dissolves the matrix and lithium salt into an organic solvent, adds nano fillers and plasticizers, and casts the membrane on a polytetrafluoroethylene plate to form a film, and the prepared electrolyte membrane meets the requirements of polymer electrolytes for all-solid-state lithium-ion batteries. However, the copolymerization reaction time of PEO and PMMA in the preparation method is too long, and is not suitable for continuous production.

[0006] CN114006032A discloses a method for preparing a solid polymer electrolyte membrane, which comprises adding aromatic polyamide pulp to a mixture of a polymer, an organic solvent and a lithium salt, and then coating and drying to obtain a polymer electrolyte membrane. The method uses a large amount of organic solvent, forms a membrane by volatilizing the solvent under high temperature conditions, and the drying time is long. Therefore, the method has the disadvantages of high energy consumption, low preparation efficiency, and environmental pollution. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of low ion conductivity and low film-forming efficiency of polymer solid electrolyte membrane in the prior art.

[0008] The inventor of the present invention found in the research process that by introducing a second solvent to prepare a polymer solid electrolyte membrane, the difference in the solubility state of the polymer in different solvents is used to quickly fix the motion state of the polymer molecular chain, thereby achieving the purpose of reducing the crystallinity of the polymer; at the same time, the addition of the second solvent can make the polymer molecules in the dissolved state quickly precipitate and solidify, avoiding the solvent volatilization process of the traditional high-temperature solvent method, reducing energy consumption and environmental pollution, and facilitating the secondary recovery of the solvent. In view of this, the present invention provides the following technical solution.

[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a polymer solid electrolyte membrane, the method comprising:

[0010] (1) mixing a polymer, a lithium salt, a plasticizer and a first solvent to obtain a polymer solid electrolyte solution; the first solvent is at least one of good solvents;

[0011] (2) applying the polymer solid electrolyte solution on a substrate to obtain a substrate I containing the electrolyte solution;

[0012] (3) placing the substrate I in a second solvent for precipitation treatment to obtain the polymer solid electrolyte membrane; the second solvent is at least one of poor solvents;

[0013] The volume ratio of the first solvent to the second solvent is 1:0.2-5.

[0014] The second aspect of the present invention provides a polymer solid electrolyte membrane prepared by the method described in the first aspect.

[0015] The third aspect of the present invention provides a solid-state lithium metal battery, which contains a positive electrode sheet, a negative electrode sheet and the polymer solid electrolyte membrane described in the second aspect.

[0016] The above technical solution of the present invention has at least the following advantages over the prior art:

[0017] (1) The polymer solid electrolyte membrane provided by the present invention has the same film-forming effect as the traditional process, low crystallinity and high ionic conductivity.

[0018] (2) The preparation method of the polymer solid electrolyte membrane provided by the present invention effectively reduces the crystallization ability of the polymer electrolyte membrane by introducing a second solvent, thereby achieving the purpose of improving the room temperature ionic conductivity of the polymer electrolyte membrane; at the same time, the film forming efficiency of the polymer solid electrolyte membrane is improved.

[0019] (3) The preparation method of the polymer solid electrolyte membrane provided by the present invention avoids the solvent volatilization process of the traditional high-temperature solvent method, reduces energy consumption and environmental pollution caused by the volatilization of organic solvents, and is conducive to the secondary recovery of solvents.

[0020] (4) The preparation method of the polymer solid electrolyte membrane provided by the present invention is flexible and diverse, applicable to a variety of situations and has the potential for continuous production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a scanning electron microscope image of the polymer solid electrolyte membrane obtained in Example 1 of the present invention;

[0022] Figure 2 is a scanning electron microscope image of the polymer solid electrolyte membrane obtained in Comparative Example 1 of the present invention;

[0023] Figure 3 1 is a DSC thermogram of the polymer solid electrolyte membrane obtained in Example 1 of the present invention and Comparative Example 1;

[0024] Figure 4 is an impedance (EIS) curve diagram of the polymer solid electrolyte membrane obtained in Example 1 of the present invention and Comparative Example 1;

[0025] Figure 5 It is a charge and discharge curve diagram of the polymer solid electrolyte membrane obtained by the application example of the present invention and the comparative application example. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] As mentioned above, the first aspect of the present invention provides a method for preparing a polymer solid electrolyte membrane, the method comprising:

[0028] (1) mixing a polymer, a lithium salt, a plasticizer and a first solvent to obtain a polymer solid electrolyte solution; the first solvent is at least one of good solvents;

[0029] (2) applying the polymer solid electrolyte solution on a substrate to obtain a substrate I containing the electrolyte solution;

[0030] (3) placing the substrate I in a second solvent for precipitation treatment to obtain the polymer solid electrolyte membrane; the second solvent is at least one of poor solvents;

[0031] The volume ratio of the first solvent to the second solvent is 1:0.2-5.

[0032] In the present invention, the "good solvent" refers to a solvent that has a strong solubility for polymer solutes and an interaction parameter with the polymer solute greater than or equal to 0.5, and the "poor solvent" refers to a solvent that has a weak solubility for polymer solutes and an interaction parameter with the polymer solute less than 0.5.

[0033] The inventors of the present invention discovered during the research process that in the process of preparing the polymer solid electrolyte membrane by introducing a second solvent, the dissolution process of the polymer in the first solvent (good solvent) is mainly divided into two steps: in the first step, the first solvent molecules first diffuse into the outer layer of the polymer and gradually enter the inner layer of the polymer from the outer layer, causing the polymer to swell, and then the polymer macromolecules gradually enter the first solvent until a uniform solution is formed, thereby achieving complete dissolution; in the second step, a second solvent (poor solvent) is added to the dissolved polymer solution, the first solvent and the second solvent are mutually soluble, the polymer molecular chains lose the dissolution environment, the molecular chain structure is quickly fixed and precipitated, and the polymer solid electrolyte membrane is formed.

[0034] The inventors of the present invention further discovered that in the process of preparing the polymer solid electrolyte membrane, the relaxation time of the polymer molecular chain is shortened, resulting in insufficient time to form crystal regions, thereby achieving the purpose of reducing the crystallinity of the polymer; at the same time, the first solvent and the second solvent are mutually soluble in each other, allowing the solvent to be quickly extracted, thereby eliminating the need for subsequent high-temperature solvent volatilization treatment.

[0035] Preferably, the volume ratio of the first solvent to the second solvent is 1:0.2-2. In this preferred case, the method for preparing a polymer solid electrolyte membrane provided by the present invention has higher film forming efficiency, lower crystallinity and higher ionic conductivity of the prepared polymer solid electrolyte membrane.

[0036] Preferably, the first solvent is at least one of water, ethanol, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, toluene, and xylene. The N-methylpyrrolidone is also known as "NMP", the N,N-dimethylformamide is also known as "DMF", and the N,N-dimethylacetamide is also known as "DMAC".

[0037] Preferably, in step (1), in the polymer solid electrolyte solution, the content of the first solvent is 70-98% by volume based on the total volume of the polymer solid electrolyte solution.

[0038] Preferably, the second solvent is at least one of water, ethanol, ethylene glycol, diethylene glycol, 1,3-butanediol, acetone, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, toluene and xylene.

[0039] Preferably, the weight ratio of the polymer, the lithium salt and the plasticizer is 12-18: 2-6: 1. In this preferred embodiment, the polymer solid electrolyte membrane prepared by the method for preparing a polymer solid electrolyte membrane provided by the present invention has lower crystallinity and higher ion conductivity.

[0040] It should be noted that the aforementioned “polymer” in the present invention refers to soluble polymer solid powder and polymer liquid having lithium ion conducting function.

[0041] Preferably, the polymer is at least one of polyether, polyester, polyolefin, polyvinylidene fluoride and polyacrylonitrile; or, the polymer is a copolymer formed by at least two monomers of ethylene oxide, olefin, vinylidene fluoride and alkane. The polyvinylidene fluoride is also known as "PVDF" and the polyacrylonitrile is also known as "PAN".

[0042] Preferably, in the polymer, the polyether is at least one of polyethylene oxide, polypropylene oxide, polybutylene oxide and polyethylene glycol dimethyl ether. The polyethylene oxide is also called "PEO".

[0043] Preferably, in the polymer, the polyester is at least one of polymethyl methacrylate, polycaprolactone, polypropylene carbonate, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate. The polymethyl methacrylate is also known as "PMMA".

[0044] Several particularly preferred embodiments of the present invention are provided below:

[0045] Preferred embodiment 1: the polymer is polyethylene oxide, the first solvent is at least one of acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, and the second solvent is ethylene glycol.

[0046] Preferred embodiment 2: the polymer is polyethylene oxide, the first solvent is acetonitrile, and the second solvent is at least one of ethanol, diethylene glycol, and 1,3-butanediol.

[0047] Preferred embodiment 3: the polymer is polyvinylidene fluoride, the first solvent is N-methylpyrrolidone, and the second solvent is ethylene glycol.

[0048] Preferred embodiment 4: the polymer is polymethyl methacrylate, the first solvent is toluene, and the second solvent is acetone.

[0049] Preferred embodiment 5: the polymer is polyacrylonitrile, the first solvent is N,N-dimethylformamide, and the second solvent is water.

[0050] The inventors of the present invention have found that in the aforementioned preferred specific embodiments 1-5, the preparation method of the polymer solid electrolyte membrane provided by the present invention can not only fix the motion state of the polymer molecular chains more quickly to obtain a polymer solid electrolyte membrane with lower crystallinity; but also further avoid the solvent volatilization process of the traditional high-temperature solvent method, thereby reducing energy consumption and pollution to the environment.

[0051] Preferably, the lithium salt is at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium trifluoromethylsulfonyl imide, lithium bis(fluorosulfonyl imide), lithium fluoromalonate borate, and lithium difluorooxalatoborate. The lithium trifluoromethylsulfonyl imide is also known as "LiTFSI".

[0052] Preferably, the plasticizer is at least one of dibutyl sebacate, dioctyl phthalate, succinonitrile and polyethylene glycol.

[0053] Preferably, in step (1), the first mixing conditions include: a mixing temperature of 20-60° C. and a mixing time of 0.5-24 h.

[0054] Preferably, in step (1), the stirring speed of the first mixing is 1800 rpm-2500 rpm.

[0055] According to a preferred embodiment, in step (2), the coating method is at least one of solution casting, blade coating, spin coating and spray coating.

[0056] According to a particularly preferred embodiment, in step (2), the substrate is at least one of an aluminum foil substrate, a copper foil substrate, a polyethylene substrate, a polypropylene substrate, a polytetrafluoroethylene substrate, a polyethylene terephthalate substrate, and a polycarbonate substrate.

[0057] Preferably, in step (2), on the substrate I, the thickness of the polymer solid electrolyte solution layer is 20 μm-3000 μm; more preferably, 1800 μm-2500 μm.

[0058] Preferably, in step (3), the method of placing the substrate I in the second solvent includes: directly immersing the substrate I in the second solvent; or placing the substrate I in a steam atmosphere in the second solvent.

[0059] Preferably, in step (3), the precipitation treatment conditions include: temperature of 10-45° C. and time of 1-8 min.

[0060] According to a preferred embodiment, step (3) further comprises: removing the solvent in the polymer solid electrolyte membrane obtained by the second mixing.

[0061] Preferably, step (3) further comprises: drying the polymer solid electrolyte membrane.

[0062] More preferably, the drying treatment conditions include: drying temperature of 20-200° C., and drying time of 10-15 h.

[0063] As mentioned above, the second aspect of the present invention provides a polymer solid electrolyte membrane prepared by the method described in the first aspect.

[0064] Preferably, the polymer solid electrolyte membrane contains 15-80 wt % of polymer.

[0065] Preferably, the polymer solid electrolyte membrane contains 15-40 wt % of lithium salt.

[0066] Preferably, the polymer solid electrolyte membrane contains 10-50 wt % of a plasticizer.

[0067] The types of polymer, lithium salt and plasticizer described in the second aspect of the present invention are the same as those described in the first aspect, and the present invention will not be repeated here.

[0068] As mentioned above, the third aspect of the present invention provides a solid-state lithium metal battery, which contains a positive electrode sheet, a negative electrode sheet and the polymer solid electrolyte membrane described in the second aspect.

[0069] Preferably, in the solid-state lithium metal battery, the polymer solid electrolyte membrane is placed between the positive electrode sheet and the negative electrode sheet.

[0070] Preferably, in the solid-state lithium metal battery, the positive electrode sheet contains a positive electrode active material, a conductive agent, and a binder.

[0071] Preferably, in the positive electrode sheet, the positive electrode active material is at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, and lithium titanate. The lithium nickel cobalt manganese oxide is also known as "NCM".

[0072] Preferably, in the positive electrode sheet, the conductive agent is at least one of activated carbon, carbon black, Super P, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, and graphene.

[0073] The present invention has no special requirements for the specific preparation process of the solid-state lithium metal battery. Those skilled in the art can prepare it by using the method for preparing solid-state lithium metal batteries known in the art. The present invention will not be repeated here, and those skilled in the art should not understand it as a limitation of the present invention.

[0074] The present invention will be described in detail below by way of examples.

[0075] In the following examples and comparative examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels. In particular, unless otherwise specified, the reagents used are commercially available analytically pure products.

[0076] Polyethylene oxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a viscosity average molecular weight (Mv) of 5 million, a CAS number of 68441-17-8, and a brand / model of P101347.

[0077] Polyvinylidene fluoride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a weight average molecular weight (Mw) of 400,000, a CAS number of 24937-79-9, and a brand / model of P169015.

[0078] Polymethyl methacrylate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a weight average molecular weight (Mw) of 350,000, a CAS number of 9011-14-7, and a brand / model of P434522.

[0079] Polyacrylonitrile was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a CAS number of 25014-41-9 and a brand / model of P303197.

[0080] Lithium trifluoromethylsulfonyl imide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with CAS number 90076-65-6 and brand / model B398978.

[0081] Succinonitrile and acetonitrile were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and acetonitrile was anhydrous grade.

[0082] Lithium nickel cobalt manganese oxide was purchased from Guangdong Kelude New Energy Technology Co., Ltd. with a brand / model of MA-EN-CA-0B.

[0083] Super P was purchased from Guangdong Kelude New Energy Technology Co., Ltd. with the brand / model number MA-EN-CO-01.

[0084] In the following examples and comparative examples, the relevant characteristic parameters were measured by the following methods:

[0085] (1) Microstructure: measured by a Hillsboro scanning electron microscope.

[0086] (2) Crystallinity: The melting enthalpy change of the prepared polymer solid electrolyte membrane was tested using a differential scanning calorimeter in a temperature range of -20 to 120 °C and a heating rate of 10 °C / min.

[0087] Then according to the formula χ c =ΔH / (χΔH*), where χ c is the crystallinity (%); ΔH* is the change in melting enthalpy of the polymer in the fully crystalline state, in J / g; ΔH is the change in melting enthalpy of the polymer sample, in J / g; χ is the mass proportion of the polymer in the electrolyte membrane (%).

[0088] (3) Ionic conductivity: The prepared polymer solid electrolyte membrane was cut into discs with a diameter of 19 mm. The discs were sandwiched between two stainless steel gaskets to assemble a symmetrical cell. The cells were then connected to an electrochemical workstation for bulk impedance testing. All impedance spectra were tested at room temperature (25 °C) to obtain the bulk impedance values ​​of the samples to be tested.

[0089] Finally, according to the formula σ=h / (AR b ) to calculate the ionic conductivity, where σ is the ionic conductivity, in S / cm; h is the thickness of the sample to be tested, in cm; A is the area of ​​the sample to be tested, in cm 2 ; R b is the body impedance of the sample to be tested, in Ω.

[0090] (4) Battery capacity utilization: The assembled button cell was charged and discharged on a Blue Power workstation, with the voltage range set to 3-4.2V, the test temperature set to 25°C, the current ratio set to 0.1C, and the battery charge and discharge curves recorded to obtain the battery capacity utilization.

[0091] Examples 1-16 are used to illustrate the polymer solid electrolyte membrane and the preparation method thereof provided by the present invention.

[0092] Example 1

[0093] (1) A polymer, a lithium salt (lithium trifluoromethylsulfonyl imide), a plasticizer (succinonitrile, 0.5 g) and a first solvent (240 mL) are first mixed to obtain a polymer solid electrolyte solution; the first solvent is at least one of the good solvents; wherein:

[0094] The types of polymer and first solvent are shown in Table 1, and the weight ratio of polymer, lithium salt and plasticizer is shown in Table 1 (unless otherwise specified, the amount of plasticizer in each example is 0.5 g, and the amount of first solvent is 240 mL);

[0095] In the polymer solid electrolyte solution, the content of the first solvent is 95 volume % based on the total volume of the polymer solid electrolyte solution;

[0096] The first mixing conditions include: mixing temperature of 25°C and mixing time of 2h;

[0097] The stirring speed of the first mixing was 2000 rpm.

[0098] (2) applying the polymer solid electrolyte solution on a substrate (polyethylene terephthalate substrate) by a doctor blade coating method to obtain a substrate I containing the electrolyte solution; wherein:

[0099] On the substrate I, the thickness of the polymer solid electrolyte solution layer is 2000 μm.

[0100] (3) immersing the substrate I in a second solvent for precipitation treatment to obtain a polymer solid electrolyte membrane, and placing the obtained polymer solid electrolyte membrane in a vacuum oven for drying treatment; the second solvent is at least one of the poor solvents; wherein:

[0101] The type of the second solvent is shown in Table 1;

[0102] The volume ratio of the first solvent to the second solvent is shown in Table 1;

[0103] The conditions of the precipitation treatment included: temperature of 25°C and time of 3 min;

[0104] The drying conditions include: drying temperature of 110° C. and drying time of 12 h.

[0105] Example 2-16

[0106] According to the method of Example 1, polymer solid electrolyte membranes were obtained respectively, except for the differences shown in Table 1 and the rest being the same.

[0107] Comparative Example 1

[0108] The method of Example 1 was followed, except that the second solvent was not added;

[0109] Step (3) is specifically as follows: placing the substrate I obtained in step (2) in a forced air oven, drying at 110° C. for 12 h to completely evaporate the solvent, and then transferring to a vacuum oven, vacuum drying at 90° C. for 12 h to obtain a polymer solid electrolyte membrane.

[0110] Comparative Examples 2-4

[0111] A similar method to that of Comparative Example 1 was used, except that the types of the first solvent were different (see Table 1), and polymer solid electrolyte membranes were obtained respectively.

[0112] Comparative Example 5

[0113] A polymer solid electrolyte membrane was obtained by adopting a method similar to that of Comparative Example 1, except that the types of the polymer and the first solvent were different (see Table 1).

[0114] Comparative Example 6

[0115] A polymer solid electrolyte membrane was obtained by following the method of Example 1, except that the volume ratio of the first solvent to the second solvent was different (see Table 1).

[0116] Table 1

[0117] polymer <![CDATA[Weight ratio 1 > First solvent Secondary solvent <![CDATA[Volume ratio 1 > Example 1 PEO 15:4:1 Acetonitrile Ethylene glycol 1:2 Example 2 PEO 15:4:1 Acetonitrile Ethylene glycol 1:1.5 Example 3 PEO 15:4:1 Acetonitrile Ethylene glycol 1:1 Example 4 PEO 15:4:1 Acetonitrile Ethylene glycol 1:0.5 Example 5 PEO 15:4:1 NMP Ethylene glycol 1:0.5 Example 6 PEO 15:4:1 DMF Ethylene glycol 1:0.5 Example 7 PEO 15:4:1 DMAC Ethylene glycol 1:0.5 Example 8 PEO 15:4:1 Acetonitrile Ethanol 1:2 Example 9 PEO 15:4:1 Acetonitrile Diethylene glycol 1:2 Example 10 PEO 15:4:1 Acetonitrile 1,3-Butanediol 1:2 Embodiment 11 PVDF 15:4:1 NMP Ethylene glycol 1:2 Example 12 PMMA 15:4:1 Toluene acetone 1:2 Example 13 PAN 15:4:1 DMF water 1:2 Embodiment 14 PEO 15:4:1 Acetonitrile Ethylene glycol 1:2.5 Embodiment 15 PEO 19:4:1 Acetonitrile Ethylene glycol 1:2 Example 16 PEO 15:4:1 Acetonitrile glycerin 1:2 Comparative Example 1 PEO 15:4:1 Acetonitrile / / Comparative Example 2 PEO 15:4:1 NMP / / Comparative Example 3 PEO 15:4:1 DMF / / Comparative Example 4 PEO 15:4:1 DMAC / / Comparative Example 5 PVDF 15:4:1 NMP / / Comparative Example 6 PEO 15:4:1 Acetonitrile Ethylene glycol 1:0.1

[0118] Note: PEO is polyethylene oxide, NMP is N-methylpyrrolidone, PVDF is polyvinylidene fluoride, PMMA is polymethyl methacrylate, PAN is polyacrylonitrile, DMF is N,N-dimethylformamide, DMAC is N,N-dimethylacetamide; weight ratio 1 is the weight ratio of polymer, lithium salt and plasticizer, volume ratio 1 is the volume ratio of the first solvent to the second solvent.

[0119] Test Case

[0120] The polymer solid electrolyte membrane prepared in the examples was tested for performance, including microstructure, crystallinity and ionic conductivity, and the results are shown in Table 2. Among them:

[0121] The present invention exemplarily provides a scanning electron microscope image of the polymer solid electrolyte membrane of Example 1, as shown in FIG. Figure 1 As shown; and the scanning electron microscope image of the polymer solid electrolyte membrane of Comparative Example 1, as Figure 2 shown.

[0122] Compare Figure 1 and Figure 2 It can be seen that the film-forming effect of the polymer solid electrolyte membrane of Example 1 is consistent with the traditional process, and its surface is flat and dense without pores and voids; the polymer solid electrolyte membrane of Comparative Example 1 has obvious surface wrinkles and particle defects, which can easily induce stress concentration and lead to electrolyte membrane rupture and battery cell short circuit. This shows that the polymer solid electrolyte membrane prepared by the preparation method of the polymer solid electrolyte membrane provided by the present invention has a uniform structure and is more conducive to the transmission of lithium ions.

[0123] The present invention also exemplarily provides the DSC thermograms of the polymer solid electrolyte membranes of Example 1 and Comparative Example 1, as shown in FIG. Figure 3 As shown. Figure 3It can be calculated that the melting exothermic enthalpy of the polymer in Example 1 is 47.373 J / g, and the melting exothermic enthalpy of Comparative Example 1 is 54.757 J / g; according to the formula, the crystallinity of Example 1 is 34.36%, and the crystallinity of Comparative Example 1 is 44.13%. It can be seen that the preparation method of the polymer solid electrolyte membrane provided by the present invention can effectively reduce the crystallinity of the polymer solid electrolyte membrane.

[0124] The present invention exemplarily provides the impedance (EIS) curves of the polymer solid electrolyte membranes of Example 1 and Comparative Example 1, as shown in FIG. Figure 4 As shown in the figure, the horizontal axis "z'" represents the real part of the impedance, and the vertical axis "z" represents the imaginary part of the impedance. Figure 4 It can be seen that the body impedance of Example 1 is 23Ω, and the body impedance of Comparative Example 1 is 55Ω; after calculation, it can be obtained that the ionic conductivity of Example 1 is 1.11×10 -4 S / cm, the ionic conductivity of comparative example 1 is 4.61×10 -5 S / cm. This indicates that the preparation method of the polymer solid electrolyte membrane provided by the present invention can effectively improve the ionic conductivity of the polymer solid electrolyte membrane.

[0125] Table 2

[0126]

[0127]

[0128] Application Examples

[0129] First, 15 g of lithium nickel cobalt manganese oxide, 3.4 g of polyethylene oxide, 0.6 g of lithium trifluoromethylsulfonyl imide and 1 g of Super P were weighed, and 113 g of N-methylpyrrolidone was added for homogenization to obtain a uniform slurry, and the slurry was coated with a 1500 μm scraper, and then placed in a 90° C. vacuum oven for 10 h to obtain a positive electrode sheet, and the positive electrode sheet was cold rolled, cut into pieces, and weighed to obtain a positive electrode sheet for button battery assembly;

[0130] Then, the polymer solid electrolyte membrane prepared in Example 1 was cut into discs with a diameter of 19 mm for assembly of button cells;

[0131] Finally, referring to the method for assembling a solid-state battery in CN115663277A, the negative electrode shell, spring, stainless steel gasket, negative electrode sheet (lithium sheet), polymer solid electrolyte membrane, positive electrode sheet, and positive electrode shell are assembled in sequence into a button battery, i.e., a solid-state lithium metal battery.

[0132] Comparative Application Examples

[0133] According to the method of the application example, the difference is that the polymer solid electrolyte membrane prepared in Comparative Example 1 is cut into round pieces with a diameter of 19 mm for assembling button batteries to obtain button batteries, namely solid-state lithium metal batteries.

[0134] The present invention exemplarily provides charge and discharge curves of polymer solid electrolyte membranes of application examples and comparative application examples, such as Figure 5 As shown. Figure 5 It can be seen that the discharge gram capacity of the solid-state lithium metal battery obtained in the application example is 203.3 mAh / g, and the discharge gram capacity of the solid-state lithium metal battery obtained in the comparative application example is 169.9 mAh / g. This indicates that the polymer solid electrolyte membrane prepared by the preparation method of the polymer solid electrolyte membrane provided by the present invention is more conducive to the performance of the gram capacity of the all-solid-state battery.

[0135] It can be seen from the above results that the film-forming effect of the polymer solid electrolyte membrane provided by the present invention is consistent with the traditional process, and has low crystallinity and high ion conductivity.

[0136] At the same time, the polymer solid electrolyte membrane provided by the present invention is assembled into a button battery in sequence with a negative electrode shell, a spring, a stainless steel gasket, a negative electrode sheet (lithium sheet), a positive electrode sheet, and a positive electrode shell. The solid-state lithium metal battery thus assembled has better battery capacity.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a polymer solid electrolyte membrane, characterized in that: The method includes: (1) mixing a polymer, a lithium salt, a plasticizer and a first solvent to obtain a polymer solid electrolyte solution; the first solvent is at least one of good solvents; (2) applying the polymer solid electrolyte solution on a substrate to obtain a substrate I containing the electrolyte solution; (3) placing the substrate I in a second solvent for precipitation treatment to obtain the polymer solid electrolyte membrane; the second solvent is at least one of poor solvents; The volume ratio of the first solvent to the second solvent is 1:0.2-5.

2. The method according to claim 1, wherein: The volume ratio of the first solvent to the second solvent is 1:0.2-2; Preferably, the first solvent is at least one of water, ethanol, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, toluene and xylene; Preferably, in step (1), in the polymer solid electrolyte solution, the content of the first solvent is 70-98% by volume based on the total volume of the polymer solid electrolyte solution.

3. The method according to claim 1 or 2, wherein: The weight ratio of the polymer, the lithium salt and the plasticizer is 12-18:2-6:1; And / or, the polymer is at least one of polyether, polyester, polyolefin, polyvinylidene fluoride, and polyacrylonitrile; or, the polymer is a copolymer formed by at least two monomers of ethylene oxide, olefin, vinylidene fluoride, and alkane; Preferably, in the polymer, the polyether is at least one of polyethylene oxide, polypropylene oxide, polybutylene oxide, and polyethylene glycol dimethyl ether; Preferably, in the polymer, the polyester is at least one of polymethyl methacrylate, polycaprolactone, polypropylene carbonate, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate.

4. The method according to claim 3, wherein: The polymer is polyethylene oxide, the first solvent is at least one of acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, and the second solvent is ethylene glycol; or The polymer is polyethylene oxide, the first solvent is acetonitrile, and the second solvent is at least one of ethanol, diethylene glycol, and 1,3-butanediol; or The polymer is polyvinylidene fluoride, the first solvent is N-methylpyrrolidone, and the second solvent is ethylene glycol; or The polymer is polymethyl methacrylate, the first solvent is toluene, and the second solvent is acetone; or The polymer is polyacrylonitrile, the first solvent is N,N-dimethylformamide, and the second solvent is water.

5. The method according to any one of claims 1 to 4, wherein: The lithium salt is at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium trifluoromethylsulfonyl imide, lithium bis(fluorosulfonyl)imide, lithium fluoromalonate borate, and lithium difluorooxalato borate; And / or, the plasticizer is at least one of dibutyl sebacate, dioctyl phthalate, succinonitrile and polyethylene glycol.

6. The method according to any one of claims 1 to 5, wherein: In step (1), the first mixing conditions include: mixing temperature of 20-60° C., mixing time of 0.5-24 h; Preferably, in step (2), on the substrate I, the thickness of the polymer solid electrolyte solution layer is 20 μm-3000 μm; Preferably, in step (3), the conditions of the precipitation treatment include: temperature of 10-45°C and time of 1-8 min.

7. A polymer solid electrolyte membrane prepared by the method according to any one of claims 1 to 6.

8. A solid-state lithium metal battery, characterized in that: The solid-state lithium metal battery contains a positive electrode sheet, a negative electrode sheet and the polymer solid electrolyte membrane described in claim 7.

9. The solid-state lithium metal battery according to claim 8, wherein: In the solid-state lithium metal battery, the positive electrode sheet contains a positive electrode active material, a conductive agent, and a binder.

10. The solid-state lithium metal battery according to claim 9, wherein: In the positive electrode sheet, the positive electrode active material is at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, and lithium titanate; and / or, In the positive electrode sheet, the conductive agent is at least one of activated carbon, carbon black, Super P, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, and graphene.

Citation Information

Patent Citations

  • All-solid polymer electrolyte membrane and preparation method thereof

    CN106992311A

  • Polymer composite solid electrolyte, solid electrolyte membrane and solid battery

    CN115663277A